Reporting key features in cold-adapted bacteria - Tribelli, Paula Maria (2018)
It is well known that cold environments are predominant over the Earth and there are a great number of reports analyzing bacterial adaptations to cold. Most of these works are focused on characteristics traditionally involved in cold adaptation, such as the structural adjustment of enzymes, maintenance of membrane fluidity, expression of cold shock proteins and presence of compatible solutes. Recent works based mainly on novel “omic” technologies have presented evidence of the presence of other important features to thrive in cold. In this work, we analyze cold-adapted bacteria, looking for strategies involving novel features, and/or activation of non-classical metabolisms for a cold lifestyle. Metabolic traits related to energy generation, compounds and mechanisms involved in stress resistance and cold adaptation, as well as characteristics of the cell envelope, are analyzed in heterotrophic cold-adapted bacteria. In addition, metagenomic, metatranscriptomic and metaproteomic data are used to detect key functions in bacterial communities inhabiting cold environments.